Legal and Economic Perspective of the Consumer Protection Act, 2019 in India: An Overview - Didwal, Dr. Aditi; Negi, Dr. Rachita (International Journal of Scientific Research and Management (IJSRM), 2022)
The industrial revolution in the international trade and commerce has brought a boom in the corporate sector, which results in a diversity of consumer goods to achieve the needs of the consumers and a mass of services have been made accessible to the consumers. But this industrial revolution had some disadvantages to the customer as it affected the business sovereignty. After independence, many   laws were enacted   in India for   safeguarding innocent customers   from unfair   and restrictive   trade practices   sort of   a false and   dishonourable description   regarding the character and quality of the goods. The year of 1986 witnessed, in the history of consumerism, the enactment of the Consumer Protection Act. The first ever legislation in India of its kind which solely aimed at the suffering taken consumers who are the victims of the unfair trade practices and sub-standard services rendered to them. The Objective of the Consumer Protection Act is to provide simple and speedy disposal to the cases by providing quasi-judicial machinery for the redressal of consumer disputes. After the restructuring of new Act, more consumer rights have been provided under clause (9) of section 2 of the consumer Protection Act, 2019. With the advancement of technology, it is obvious that electronic media has an important place in business world. The provision of e- commerce has also been inserted in the Act after reframing the Consumer protection act. The new Act provides for separate provisions for each thing and is well framed Act that makes it more proper. The new chapters that have been added to this act, work as a proper criterion for deciding the offences and penalties. The increase in the fiscal value along with the time needed a rise in the value of fine too. The new Act proposes effective measures and tightens the existing rules to further safeguard consumer rights. Introduction of a central regulator, strict penalties for misleading advertisements and guidelines for e-commerce and electronic service providers are some of the key highlights.